A systematic review of cost–effectiveness analyses of pharmacogenetic-guided dosing in treatment with coumarin derivatives. (July 2010) - Verhoef, Talitha I; Redekop, William K; Darba, Josep; Geitona, Mary; Hughes, Dyfrig A; Siebert, Uwe; de Boer, Anthonius; Maitland-van der Zee, Anke-Hilse; Barallon, Rita; Briz, Montserrat; Daly, Ann; Haschke-Becher, Elisabeth; et al.
Anticoagulant therapy with coumarin derivatives is often sub- or supra-therapeutic, resulting in an increased risk of thromboembolic events or hemorrhage, respectively. Pharmacogenetic-guided dosing has been proposed as an effective way of reducing bleeding rates. Clinical trials to confirm the safety, efficacy and effectiveness of this strategy are ongoing, but in addition, it is also necessary to consider the cost–effectiveness of this strategy. This article describes the findings of a systematic review of published cost–effectiveness analyses of pharmacogenetic-guided dosing of coumarin derivatives. Similarities and differences in the approaches used were examined and the quality of the analyses was assessed. The results of the analyses are not sufficient to determine whether or not pharmacogenetic-guided dosing of coumarins is cost effective. More reliable cost–effectiveness estimates need to become available before it is possible to recommend whether or not this strategy should be applied in clinical practice.